Prevalence And Associated Factors Of Job-Related Depression In Laboratory Technicians In Hospital Universiti Sains Malaysia (HUSM) And Ministry Of Health Malaysia (MOH) Hospitals In Kelantan. - Aziah, B.D.; Rusli, B.N.; T Winn, Dr PH; Tengku, M.A. (2004)

(untitled)
'Work-related depression is a clinical illness and workers should take this seriously.